The antibacterial action of Moringa oleifera: A systematic review - van den Berg, Jorrit; Kuipers, Saskia (South African journal of botany, 2022)
•Thorough systematic literature review on the subject.•Many articles written on the subject and only 12 could be used in this review.•Moderate to absent antibacterial activity was found in vitro.•More standardized research needed for accurate conclusions. This systematic review on the antibacterial activity of Moringa oleifera includes a critical analysis of available literature researching in-vitro outcomes of microbiological testing. Our main aim was to understand if Moringa oleifera can be used as an antibacterial agent in human medicine based on in-vitro testing, since antibacterial resistance is on the rise worldwide. Articles meeting the inclusion criteria were searched in three databases, EMBASE, Cochrane and PubMed, up to March 2022. This resulted in an initial search of 1005 studies, with 675 studies remaining after removal of doubles. Studies investigating combined activity of an antibiotic and Moringa oleifera were not assessed. Due to unclear procedures or lack of clearly defined results 568 studies were excluded. The remaining studies were subjected to two validity checks and one quality check, resulting in a total number of twelve included studies. In these studies, fifteen different procedures in leaves, whole seeds and dehusked seeds were described. The focus was put on the best method of extraction method that preserved antibacterial activity. Antimicrobial testing in the studies was performed with minimum inhibitory concentration testing on solid or liquid media, disk diffusion, or a combination thereof. A meta-analysis was not performed as procedures were not comparable. Whole Moringa oleifera seeds possess better antibacterial activity than dehusked seeds. Methanol leaf extract demonstrated better activity than aqueous leaf extract in inhibiting Pseudomonas aeruginosa and Klebsiella pneumoniae. In conclusion, most Moringa oleifera extracts tested in these twelve studies demonstrated minimal inhibition of bacterial growth. This may be related to drawbacks of antibacterial testing on solid media. There were unknown gaps in variables in studies assessing the concentration of extracts and the absolute quantity of moringa, besides lack of corresponding MICs and disc diffusion values. A standardized antibacterial testing format using liquid media in the future may increase data reliability. Studying the combination of Moringa oleifera with antibiotics in-vitro and in-vivo may lead to more promising results and a better understanding of how moringa can be used as a therapeutic agent in human bacterial infection.